Positive pole piece, electrochemical device and electronic device
By using a coating containing phosphate and a second inorganic component on the positive electrode plate of the electrochemical device, the problem of poor resistance of the coating at high temperatures in the prior art is solved, and higher adhesion and friction resistance are achieved. It improves the safety performance and normal working ability of the electrochemical device.
Patent Information
- Application Number
- CN202411505548.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-21
AI Technical Summary
The positive electrode coating of existing electrochemical devices has poor resistance at high temperatures, which is prone to powder loss, deformation or falling off, resulting in safety hazards and the normal operation of electrochemical devices.
A coating including phosphate and the second inorganic group is used. The phosphate has a mesh structure and high temperature tolerance. A more dense mesh structure is formed through the contraction reaction with the second inorganic group, enhancing the bonding of the coating Power and friction.
It improves the safety performance of the electrochemical device at high temperatures, reduces the risk of short circuit, ensures that the coating is not easy to fall off, protects the aluminum foil, and maintains the normal operation of the electrochemical device.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemistry, and in particular to a positive electrode sheet, an electrochemical device and an electronic device. Background Art
[0002] As the application scope of electrochemical devices (such as lithium-ion batteries) becomes wider and wider, higher requirements are placed on their safety performance. When electrochemical devices are subjected to abnormal conditions such as extrusion, collision or puncture, they are prone to fire and explosion due to short circuits in the electrochemical devices, and electrochemical devices also generate a lot of heat when working normally. As a key structure to improve the safety performance of electrochemical devices, the existing positive electrode coating has poor high temperature resistance and is prone to powder loss, deformation or even falling off at high temperatures. It does not play a role in protecting the aluminum foil and may even affect the normal operation of the electrochemical device, posing a safety hazard. Summary of the invention
[0003] In view of this, the present application provides a positive electrode plate, an electrochemical device and an electronic device.
[0004] In a first aspect, the present application provides a positive electrode plate, the positive electrode plate comprising a current collector, a positive electrode material layer, and a coating disposed between the current collector and the positive electrode material layer; the coating comprises a first inorganic component and a second inorganic component, the first inorganic component comprises a phosphate, the phosphate comprises at least one of lithium, magnesium, zinc and aluminum, and the second inorganic component is different from the first inorganic component.
[0005] In the present application, the second inorganic component is different from the first inorganic component, which means that the second inorganic component does not include phosphate substances. The present application adds phosphate and the second inorganic component to the coating. Since the phosphate itself has a network structure, it has the property of high temperature resistance; secondly, the phosphate can undergo a condensation reaction with the second inorganic component and wrap the second inorganic component to form a more dense network structure than the network structure of the phosphate itself, thereby increasing the adhesion and friction resistance of the coating at high temperatures. This dense network structure makes the coating less likely to fall off at high temperatures, reducing the risk of short circuits caused by direct contact between the positive current collector and the anode, thereby improving the safety performance of the electrochemical device.
[0006] Based on the first aspect, in some possible embodiments, the phosphate is selected from at least one of lithium dihydrogen phosphate and aluminum dihydrogen phosphate.
[0007] The above raw materials selected in the present application have relatively good strength and adhesion, and relatively good bonding performance at high temperatures. The above phosphates can be formed through dehydration condensation, thereby further improving the safety performance of the electrochemical device.
[0008] Based on the first aspect, in some possible implementations, based on the total mass of the coating, the mass percentage of the first inorganic component is A%, 5≤A≤30.
[0009] By controlling the mass percentage of the first inorganic component to meet the above range, the present application not only makes the coating have good high temperature resistance, but also reduces the probability of the coating falling off the current collector when high temperature is generated by a short circuit inside the electrochemical device; it can also reduce the phenomenon of the coating absorbing water when exposed to the air due to missing coating, and the coating has good appearance and leveling properties, further improving the safety performance of the electrochemical device.
[0010] Based on the first aspect, in some possible implementations, based on the total mass of the coating, the mass percentage of the first inorganic component is A%, the mass percentage of the second inorganic component is B%, and 1.5≤A / B≤20.
[0011] The present application controls the mass percentage ratio of the first inorganic component and the second inorganic component to meet the above-mentioned range, thereby not only reducing the risk of the first inorganic component being exposed to water absorption in the air due to excess; the first inorganic component and the second inorganic component form a denser network structure, thereby enhancing the high temperature resistance of the coating, making the coating less likely to fall off at high temperatures; and further improving the safety performance of the electrochemical device.
[0012] Based on the first aspect, in some possible implementations, within a 1 μm×1 μm region of the coating, the mass of phosphorus accounts for 1% to 6% of the mass of all elements.
[0013] Based on the first aspect, in some possible implementations, within a 1 μm×1 μm region of the coating, the mass of phosphorus accounts for 3.3% to 6% of the mass of all elements.
[0014] By controlling the mass percentage of phosphorus to meet the above range, the present application not only improves the appearance of the coating and reduces the risk of coating leakage caused by shrinkage of the coating on the current collector, but also enhances the high temperature resistance of the coating and further improves the safety performance of the electrochemical device.
[0015] Based on the first aspect, in some possible implementations, the second inorganic component includes at least one of boehmite, aluminum oxide, zinc borate, barium borate and antimony oxide.
[0016] The above-mentioned second inorganic component selected in the present application has a certain strength itself, which can improve the mechanical strength of the coating, and the first inorganic component and the second inorganic component jointly play an insulating role, avoiding the short circuit problem caused by the contact between the anode and the positive electrode material layer, and further improving the safety performance of the electrochemical device.
[0017] Based on the first aspect, in some possible implementations, the particle size Dv50 of the second inorganic component is 0.1 μm to 2 μm, and Dv90 is 2 μm to 3 μm.
[0018] In the present application, by controlling the particle size of the second inorganic component to meet the above range, the thickness of the coating layer is moderate, thereby further improving the safety performance of the electrochemical device.
[0019] Based on the first aspect, in some possible implementations, the coating further includes a second component, and the second component includes at least one of polyacrylic acid, polypropylene alcohol and sodium carboxymethyl cellulose.
[0020] The present application can improve the appearance of the coating by adding the above-mentioned second component to the coating, and the second component itself has relatively good bonding properties. Therefore, when the second component is used in combination with the first inorganic component and the second inorganic component, it is beneficial to improve the adhesion between the coating and the current collector, especially when the electrochemical device is short-circuited and high temperature is generated, the probability of coating peeling off is reduced, and the safety performance of the electrochemical device is further improved. Based on the first aspect, in some possible implementations, based on the total mass of the coating, the mass percentage of the second component is C%, 1≤C≤15.
[0021] The present application controls the mass percentage of the second component to meet the above range, so that the coating has better adhesion and is not easy to fall off from the current collector, thereby improving the high temperature resistance of the coating and further improving the safety performance of the electrochemical device.
[0022] Based on the first aspect, in some possible implementations, based on the total mass of the coating, the mass percentage of the first inorganic component is A%, the mass percentage of the second component is C%, and 1≤A / C≤4.
[0023] The present application further improves the leveling of the coating and reduces the risk of coating leakage by controlling the mass percentage ratio of the first inorganic component and the second component to meet the above-mentioned range. While improving the appearance of the coating, it also further enhances its high temperature resistance, thereby further improving the safety performance of the electrochemical device.
[0024] Based on the first aspect, in some possible implementations, the coating further includes conductive carbon, and the mass percentage of the conductive carbon is D%, based on the total mass of the coating, and 0.005≤D≤0.06.
[0025] The present application helps to improve the conductivity of the positive electrode sheet and further improves the safety performance of the electrochemical device by controlling the mass percentage of the conductive carbon to meet the above range.
[0026] Based on the first aspect, in some possible implementations, the sphericity of the conductive carbon is 0.7 to 0.9, and further, the sphericity of the conductive carbon is 0.85 to 0.95.
[0027] Based on the first aspect, in some possible implementations, the positive electrode plate is placed at room temperature, and the film resistance of the positive electrode plate is 1Ω to 8Ω.
[0028] Based on the first aspect, in some possible implementations, the positive electrode plate is placed at a temperature of 600° C. for 2 hours, and the film resistance of the positive electrode plate is 0.8Ω to 2Ω.
[0029] By controlling the membrane resistance of the positive electrode sheet to meet the above range, the present application can not only reduce the risk of large current in the circuit due to too small membrane resistance, thereby further improving the safety performance of the electrochemical device, but also reduce the impact of excessive membrane resistance on the electrical performance of the electrochemical device.
[0030] Moreover, the film resistance of the positive electrode sheet of the present application is not easy to fall off in a normal temperature or high temperature environment, and will not cause a sudden drop in the collector resistance to cause a large short-circuit current electrode assembly.
[0031] Based on the first aspect, in some possible implementations, the positive electrode sheet is placed at room temperature, and the bonding force between the coating and the current collector is 200N / m to 800N / m; the positive electrode sheet is placed at 600°C for 2h, and the bonding force between the coating and the current collector is 10N / m to 200N / m.
[0032] Based on the first aspect, in some possible implementations, the positive electrode sheet is placed at 600°C for 2 hours, and the powder loss rate of the coating is 0.3% to 8%; the positive electrode sheet is placed in dimethyl carbonate at 85°C for 2 hours, and the powder loss rate of the coating is 0.5% to 10%. It can be seen that the coating does not fall off after high temperature and still has a protective effect on the current collector.
[0033] A second aspect of the present application provides an electrochemical device, including an electrode assembly, the electrode assembly including the positive electrode plate provided in the first aspect of the present application, and the pass rate of the nail penetration test of the electrode assembly is 90% to 100%.
[0034] When the pass rate of the electrode assembly puncture test of the present application meets the above range, the safety performance of the electrochemical device is further improved.
[0035] A third aspect of the present application provides an electronic device, including the electrochemical device provided in the second aspect of the present application. The electrochemical device has good safety performance and is conducive to increasing the service life of the electronic device. DETAILED DESCRIPTION
[0036] The following examples are described in detail. The following examples are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. The reagents and materials described in the following examples can all be obtained from commercial sources.
[0037] coating An embodiment of the present application provides a coating disposed between a current collector and a positive electrode material layer, the coating comprising a first inorganic component and a second inorganic component, the first inorganic component comprising phosphate, the phosphate comprising at least one of lithium, magnesium, zinc and aluminum, and the second inorganic component being different from the first inorganic component.
[0038] In the present application, the second inorganic component is different from the first inorganic component, which means that the second inorganic component does not include phosphate substances. The present application adds a phosphate second inorganic component to the coating, and since the phosphate itself has a network structure, it has the property of high temperature resistance; secondly, the coating further contains a second inorganic component, and the phosphate can undergo a condensation reaction with the second inorganic component and wrap the second inorganic component, forming a more dense network structure than the phosphate itself has a network structure, increasing the adhesion and friction resistance of the coating at high temperatures. This dense network structure makes the coating not easy to fall off at high temperatures, reducing the risk of short circuit caused by direct contact between the positive current collector and the anode, thereby improving the safety performance of the electrochemical device.
[0039] In some embodiments, the phosphate is selected from at least one of lithium dihydrogen phosphate and aluminum dihydrogen phosphate.
[0040] The above raw materials selected in the present application have relatively good strength and adhesion, and relatively good bonding performance at high temperatures. The above phosphates can be formed through dehydration condensation, thereby further improving the safety performance of the electrochemical device.
[0041] In some embodiments, based on the total mass of the coating, the mass percentage of the first inorganic component is A%, 5≤A≤30. For example, A can be 5, 7, 10, 12, 15, 17, 20, 22, 24, 26, 28, 30 or any value within the range of any of the above values.
[0042] By controlling the mass percentage of the first inorganic component to meet the above range, the present application not only makes the coating have good high temperature resistance, but also reduces the probability of the coating falling off the current collector when high temperature is generated by a short circuit inside the electrochemical device; it can also reduce the phenomenon of the coating absorbing water when exposed to the air due to missing coating, and the coating has good appearance and leveling properties, further improving the safety performance of the electrochemical device.
[0043] In some embodiments, based on the total mass of the coating, the mass percentage of the first inorganic component is A%, the mass percentage of the second inorganic component is B%, and 1.5≤A / B≤20. For example, A / B can be any value within the range of 1.5, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20 or any value above.
[0044] The present application controls the mass percentage ratio of the first inorganic component and the second inorganic component to meet the above-mentioned range, thereby not only reducing the risk of the first inorganic component being exposed to water absorption in the air due to excess; the first inorganic component and the second inorganic component form a denser network structure, thereby enhancing the high temperature resistance of the coating, making the coating less likely to fall off at high temperatures; and further improving the safety performance of the electrochemical device.
[0045] In some embodiments, in a 1 μm×1 μm area of the coating, the mass percentage of the phosphorus element to the mass of all elements is 1% to 6%. For example, the mass percentage of phosphorus can be 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4, 4.2, 4.4, 4.6, 4.8, 5, 5.2, 5.4, 5.6, 5.8, 6 or any value in the range of any of the above values.
[0046] By controlling the mass percentage of phosphorus to meet the above range, the present application not only improves the appearance of the coating and reduces the risk of coating leakage caused by shrinkage of the coating on the current collector, but also enhances the high temperature resistance of the coating and further improves the safety performance of the electrochemical device.
[0047] In some embodiments, the second inorganic component includes at least one of boehmite, aluminum oxide, zinc borate, barium borate, and antimony oxide.
[0048] The above-mentioned second inorganic component selected in the present application has a certain strength itself, which can improve the mechanical strength of the coating, and the first inorganic component and the second inorganic component jointly play an insulating role, avoiding the short circuit problem caused by the contact between the anode and the positive electrode material layer, and further improving the safety performance of the electrochemical device.
[0049] In some embodiments, the particle size Dv50 of the second inorganic component is 0.1 μm to 2 μm, and Dv90 is 2 μm to 3 μm. For example, Dv50 can be 0.11 μm, 0.2 μm, 0.4 μm, 0.6 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm, or any value in the range of any of the above values. For example, Dv90 can be 2 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3 μm, or any value in the range of any of the above values.
[0050] In the present application, by controlling the particle size of the second inorganic component to meet the above range, the thickness of the coating layer is moderate, thereby further improving the safety performance of the electrochemical device.
[0051] In some embodiments, the coating further comprises a second component, and the second component comprises at least one of polyacrylic acid, polypropylene alcohol and sodium carboxymethyl cellulose.
[0052] The present application can improve the appearance of the coating by adding the above-mentioned second component to the coating, and the second component itself has relatively good bonding properties. Therefore, when the second component is used in combination with the first inorganic component and the second inorganic component, it is beneficial to improve the adhesion between the coating and the current collector, especially when the electrochemical device is short-circuited and high temperature is generated, the probability of coating peeling is reduced, and the safety performance of the electrochemical device is further improved. In some embodiments, based on the total mass of the coating, the mass percentage of the second component is C%, 1≤C≤15. For example, C can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15 or any value within the range consisting of any of the above values.
[0053] The present application controls the mass percentage of the second component to meet the above range, so that the coating has better adhesion and is not easy to fall off from the current collector, thereby improving the high temperature resistance of the coating and further improving the safety performance of the electrochemical device.
[0054] In some embodiments, based on the total mass of the coating, the mass percentage of the first inorganic component is A%, and the mass percentage of the second component is C%, 1≤A / C≤4. For example, A / C can be 1, 1.2, 1.4, 1.6, 1.8, 2, 2.1, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 3.9, 4 or any value within the range consisting of any of the above values.
[0055] The present application further improves the leveling of the coating and reduces the risk of coating leakage by controlling the mass percentage ratio of the first inorganic component and the second component to meet the above-mentioned range. While improving the appearance of the coating, it also further enhances its high temperature resistance, thereby further improving the safety performance of the electrochemical device.
[0056] In some embodiments, the coating further comprises conductive carbon, and the mass percentage of the conductive carbon is D%, based on the total mass of the coating, and 0.005≤D≤0.06. For example, D can be 0.005, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06 or any value within the range consisting of any of the above values.
[0057] The present application helps to improve the conductivity of the positive electrode sheet and further improves the safety performance of the electrochemical device by controlling the mass percentage of the conductive carbon to meet the above range.
[0058] In some embodiments, the sphericity of the conductive carbon is 0.7 to 0.9, and further, the sphericity of the conductive carbon is 0.85 to 0.95. For example, the sphericity of the conductive carbon can be 0.7, 0.71, 0.72, 0.73, 0.74, 0.75, 0.76, 0.78, 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, 0.91, 0.92, 0.93, 0.94, 0.95 or any value within the range of any of the above values.
[0059] In some embodiments, when the positive electrode sheet is placed at room temperature, the bonding force between the coating and the current collector is 200 N / m to 800 N / m; when the positive electrode sheet is placed at 600°C for 2 hours, the bonding force between the coating and the current collector is 10 N / m to 200 N / m.
[0060] In some embodiments, the positive electrode sheet was placed at 600°C for 2 hours, and the powder loss rate of the coating was 0.3% to 8%; the positive electrode sheet was placed in dimethyl carbonate at 85°C for 2 hours, and the powder loss rate of the coating was 0.5% to 10%. It can be seen that the coating does not fall off after high temperature and still has a protective effect on the current collector.
[0061] Positive electrode The positive electrode sheet includes a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector, and a coating of the present application is disposed on a surface of the positive electrode current collector facing the positive electrode material layer. The positive electrode current collector may be aluminum foil or nickel foil, or may be any composite current collector disclosed in the prior art, for example, including but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0062] The positive electrode material in the positive electrode material layer can be selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate and compounds obtained by adding other transition metals or non-transition metals to the above compounds.
[0063] The positive electrode material layer also includes a binder to bond the positive electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the bonding force between the positive electrode material layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to polyvinylidene fluoride, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic (ester) styrene butadiene rubber, epoxy resin or nylon, etc. At least one.
[0064] The positive electrode material layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, conductive carbon black (Super P), acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.
[0065] In some embodiments, the positive electrode sheet is placed at room temperature, and the film resistance of the positive electrode sheet is 1Ω to 8Ω.
[0066] In some embodiments, the positive electrode sheet is placed at a temperature of 600° C. for 2 hours, and the film resistance of the positive electrode sheet is 0.8Ω to 2Ω.
[0067] By controlling the membrane resistance of the positive electrode sheet to meet the above range, the present application can not only reduce the risk of large current in the circuit due to too small membrane resistance, thereby further improving the safety performance of the electrochemical device, but also reduce the impact of excessive membrane resistance on the electrical performance of the electrochemical device.
[0068] Moreover, the film resistance of the positive electrode sheet of the present application is not easy to fall off in a normal temperature or high temperature environment, and will not cause a sudden drop in the collector resistance to cause a large short-circuit current electrode assembly.
[0069] Negative electrode The negative electrode sheet of the present application includes a negative electrode current collector and a negative electrode material layer disposed on the negative electrode current collector. The negative electrode current collector may be at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode material layer includes a negative electrode material, and optionally a conductive agent, a binder and a thickener.
[0070] The negative electrode material of the present application may include at least one of a carbon material or a silicon-based material. In some embodiments, the carbon material includes but is not limited to at least one of natural graphite, artificial graphite, mesophase microcarbon spheres, hard carbon or soft carbon. In some embodiments, the silicon-based material includes but is not limited to at least one of silicon, silicon-oxygen composite materials or silicon-carbon composite materials.
[0071] The specific type of the conductive agent is not subject to specific restrictions and can be selected according to needs. As an example, the conductive agent includes but is not limited to conductive graphite, superconducting carbon, at least one of acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0072] The specific type of the binder is not subject to specific restrictions and can be selected according to needs. As an example, the binder includes but is not limited to at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), water-based acrylic resin and carboxymethyl cellulose.
[0073] The specific type of thickener is not subject to specific limitation and can be selected according to the requirements. As an example, the thickener includes but is not limited to sodium carboxymethyl cellulose (CMC).
[0074] However, the present application is not limited to the above materials, and the negative electrode plate of the present application may also use other known materials that can be used as negative electrode active materials, conductive agents, binders and thickeners.
[0075] Isolation film The material and shape of the separator used in the electrochemical device of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0076] For example, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be selected.
[0077] A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer includes a second inorganic component and a binder, and the second inorganic component is selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride and poly (vinylidene fluoride-hexafluoropropylene).
[0078] Electrolyte According to some embodiments of the present application, the electrolyte includes an organic solvent, a lithium salt and an optional additive. The organic solvent of the electrolyte according to the present application may be any organic solvent known in the prior art that can be used as a solvent for the electrolyte. The electrolyte used in the electrolyte according to the present application is not limited, and it can be any electrolyte known in the prior art. The additive of the electrolyte according to the present application can be any additive known in the prior art that can be used as an electrolyte additive.
[0079] The organic solvent includes a carbonate solvent, a carboxylate solvent or a combination thereof; wherein the carbonate solvent includes at least one of diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC) or butylene carbonate (BC). The carboxylate solvent includes at least one of ethyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl butyrate, ethyl difluoroacetate, difluoroethyl acetate, ethyl trifluoroacetate, trifluoroethyl acetate or methyl trifluoropropionate.
[0080] Lithium salts include, but are not limited to, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalatoborate) LiB(C2O4)2 (LiBOB), or lithium difluorooxalatoborate LiBF2(C2O4) (LiDFOB).
[0081] Electrochemical Devices The electrochemical device of the present application also includes a shell (such as a packaging bag) for accommodating the above-mentioned positive electrode sheet, separator, negative electrode sheet and electrolyte, as well as other components known in the electrochemical field, and the present application does not limit the above-mentioned other components. The present application has no special restrictions on the shell, which can be a shell known in the art, as long as the purpose of the present application can be achieved. For example, an aluminum-plastic film packaging bag can be used. The present application has no special restrictions on the type of chemical device, which can include any device that undergoes an electrochemical reaction. The electrochemical device containing the above-mentioned coating has good safety performance.
[0082] Electronic Devices The electrochemical device is applied to an electronic device to supply power to a load in the electronic device. Moreover, the electrochemical device has good safety performance and is conducive to improving the service life of the electronic device. Among them, the electronic device may include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0083] Example 1 <Preparation of coating> 6 kg of lithium dihydrogen phosphate, 3.2 kg of polyacrylic acid, 30 kg of boehmite and 0.24 kg of conductive carbon were added to 60 kg of deionized water and stirred at a stirring speed of 1500 rpm for 3 hours to obtain a coating slurry, which was coated on an aluminum foil to obtain an aluminum foil with a coating, which was recorded as current collector I. The current collector I was dried at 120° C. to obtain a current collector coated on one side, and then the above steps were repeated on the other surface of the aluminum foil to obtain a current collector coated on both sides.
[0084] <Preparation of positive electrode sheet> The binder polyvinylidene fluoride (PVDF), the conductive agent conductive carbon black (Super P), the positive electrode material lithium nickel cobalt manganese oxide (LiNi 08 Co 01 Mn 01 O2) are mixed evenly in a weight ratio of 2:2:96 to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the coating of the above-mentioned current collector with a thickness of 10μm, and dried at 120°C for 1 hour to obtain a positive electrode sheet coated with a positive electrode material layer with a thickness of 60μm on one side. Repeat the above steps on the coating on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Dry under vacuum conditions at 120°C for 1 hour, then cold press, cut pieces, and weld the pole ears to obtain a positive electrode sheet with a specification of 74mm×867mm.
[0085] <Preparation of negative electrode sheet> After mixing the negative electrode active material graphite, thickener sodium carboxymethyl cellulose (CMC-Na), and binder styrene-butadiene rubber (SBR) in a weight ratio of 96:2:2, deionized water was added, and the mixture was stirred to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry was 75wt%; the negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12μm, and dried at 120°C to obtain a negative electrode sheet with a coating thickness of 80μm and a single-sided negative electrode material layer. Repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided negative electrode material layer. Dry under vacuum conditions at 120°C for 1 hour, and then obtain a negative electrode sheet with a specification of 78mm×875mm after cold pressing, cutting, and slitting.
[0086] <Preparation of Electrolyte> In an argon atmosphere glove box with a water content of <10ppm, propylene carbonate (PC), ethylene carbonate (EC), and diethyl carbonate (DEC) were mixed in a mass ratio of 1:1:1, and then fully dried lithium salt LiPF6 was dissolved in the above non-aqueous solvent to prepare the electrolyte in the embodiment. Based on the mass of the electrolyte, the mass proportion of LiPF6 is 13%.
[0087] <Preparation of Separator Film> A polyethylene (PE) porous polymer film with a thickness of 7 μm was used as the isolation membrane.
[0088] Preparation of electrochemical device The positive electrode sheet, separator, and negative electrode sheet prepared above are stacked in sequence, and then wound to obtain an electrode assembly. After the tabs are welded, the electrode assembly is placed in an aluminum-plastic film, dried in a vacuum oven at 80°C for 12 hours to remove moisture, and then injected with the above-configured electrolyte. After vacuum packaging, standing, formation (1.5C constant current charging to 4.35V, then 0.05C constant current charging to 4.5V), capacity, shaping and other processes, an electrochemical device is obtained.
[0089] Example 2 The difference between Example 2 and Example 1 is that the lithium dihydrogen phosphate in <Preparation of coating> is replaced by magnesium dihydrogen phosphate, and the other conditions / preparation methods are the same as those in Example 1. The above specific preparation parameters can be adjusted accordingly according to Table 1.
[0090] Example 3 The difference between Example 3 and Example 1 is that the lithium dihydrogen phosphate in <Preparation of coating> is replaced by zinc dihydrogen phosphate, and the other conditions / preparation methods are the same as those in Example 1. The above specific preparation parameters can be adjusted accordingly according to Table 1.
[0091] Example 4 The difference between Example 4 and Example 1 is that the lithium dihydrogen phosphate in <Preparation of coating> is replaced by aluminum dihydrogen phosphate, and the other conditions / preparation methods are the same as those in Example 1. The above specific preparation parameters can be adjusted accordingly according to Table 1.
[0092] Example 5 The difference between Example 5 and Example 1 is that the lithium dihydrogen phosphate in <Preparation of coating> is replaced by lithium dihydrogen phosphate and aluminum dihydrogen phosphate, and the other conditions / preparation methods are the same as those in Example 1. The above specific preparation parameters can be adjusted accordingly according to Table 1.
[0093] Examples 6 to 9 The difference between Examples 6 to 9 and Example 4 is that the content of the first inorganic component is adjusted, and the other conditions / preparation methods are the same as those of Example 4. The above specific preparation parameters can be adjusted accordingly according to Table 1.
[0094] Examples 10 to 13 The difference between Examples 10 to 13 and Example 4 is that the phosphorus content of the phosphate in the first inorganic component is adjusted, and the other conditions / preparation methods are the same as those of Example 4. The above specific preparation parameters can be adjusted accordingly according to Table 1.
[0095] Examples 14 to 17 The difference between Examples 14 to 17 and Example 4 is that the content of the first inorganic component and the content of the second inorganic component are adjusted, and the other conditions / preparation methods are the same as those of Example 4. The above specific preparation parameters can be adjusted accordingly according to Table 3.
[0096] Embodiment 18 The difference between Example 18 and Example 4 is that boehmite in <Preparation of coating> is replaced by alumina, and the other conditions / preparation methods are the same as those in Example 4. The above specific preparation parameters can be adjusted accordingly according to Table 3.
[0097] Examples 19 to 26 The difference between Examples 19 to 26 and Example 4 is that the particle size Dv50 and Dv90 of the second inorganic component are adjusted, and the other conditions / preparation methods are the same as those of Example 4. The above specific preparation parameters can be adjusted accordingly according to Table 3.
[0098] Embodiment 27 The difference between Example 27 and Example 4 is that the polyacrylic acid in <Preparation of coating> is replaced by polypropylene alcohol, and the other conditions / preparation methods are the same as those in Example 4. The above specific preparation parameters can be adjusted accordingly according to Table 5.
[0099] Embodiment 28 The difference between Example 28 and Example 4 is that the polyacrylic acid in <Preparation of coating> is replaced by sodium carboxymethyl cellulose (CMC-Na), and the other conditions / preparation methods are the same as those in Example 4. The above specific preparation parameters can be adjusted accordingly according to Table 5.
[0100] Examples 29 to 32 The difference between Examples 29 to 32 and Example 4 is that the content of the second component is adjusted, and the other conditions / preparation methods are the same as those of Example 4. The above specific preparation parameters can be adjusted accordingly according to Table 5.
[0101] Examples 33 to 36 The difference between Examples 33 to 36 and Example 4 is that the content of the first inorganic component and the content of the second component are adjusted, and the other conditions / preparation methods are the same as those of Example 4. The above-mentioned specific preparation parameters can be adjusted accordingly according to Table 5.
[0102] Comparative Example 1 The difference between Comparative Example 1 and Example 4 is that aluminum dihydrogen phosphate is not added in <Preparation of Coating>, and the other conditions / preparation methods are the same as those in Example 4. The above specific preparation parameters can be adjusted accordingly according to Table 7.
[0103] Comparative Example 2 The difference between Comparative Example 2 and Example 4 is that boehmite is not added in <Preparation of Coating>, and the other conditions / preparation methods are the same as those of Example 4. The above specific preparation parameters can be adjusted accordingly according to Table 7.
[0104] Comparative Example 3 The difference between Comparative Example 3 and Example 4 is that aluminum dihydrogen phosphate and boehmite are not added in <Preparation of Coating>, and the other conditions / preparation methods are the same as those in Example 4. The above specific preparation parameters can be adjusted accordingly according to Table 7.
[0105] Test Method 1. Test method for component content in coating (1) FTIR test: The current collector coating was subjected to FTIR detection. The characteristic chemical bond of the first inorganic component, PO4 stretching vibration, was detected at 1000 cm -1 Up to 1100cm -1 , P-OH stretching vibration at 900 cm -1 Up to 950 cm -1 , the absorption peak of Al-OP is at 500 cm -1 Up to 700 cm -1 .
[0106] (2) DSC test: (a) Sample pretreatment: After the battery cell is removed, place the current collector and current collector coating without the positive electrode material layer in a fume hood to dry for 2 hours, and cut out a 2cm×2cm area, weigh its weight m1, immerse the cut piece in DI aqueous solution, wash off the coating, weigh the current collector weight m2, then the coating mass m=m1-m2; (b) Take the current collector and current collector coating without the positive electrode material layer. Place them in the sample crucible, place the sample crucible and the reference crucible (empty crucible) together in the DSC instrument, set the heating rate to 10℃ / min, and the temperature to 25℃ to 800℃; (c) Start the DSC instrument and heat the sample crucible and the reference crucible at the same time, and the DSC will automatically measure the temperature difference between the two. A curve with temperature as the horizontal axis and heat flow as the vertical axis is obtained. The first inorganic component will show an obvious endothermic peak between 250℃ and 400℃, and its peak area Q is calculated; (d) The content of the first inorganic component = Q / △H, where △H is the decomposition enthalpy; (e) Determination of decomposition enthalpy △H: Take 10 mg of aluminum dihydrogen phosphate standard sample, put it into the DSC sample crucible, and heat up at a rate of 10℃ / min from 25℃ to 800℃. Record the area of the decomposition peak Q2, then △H=Q2 / 10 / 1000 (J / g).
[0107] 2. Particle size test method of the second inorganic component (1) Sample pretreatment: After the electrode assembly is removed, place the current collector without the positive electrode material layer in a fume hood to air dry for 2 hours. First, use water to dissolve the phosphate and cut out an area larger than 1 cm × 1 cm for electron microscope scanning; (2) Test process: Turn on the power of the water chiller until the displayed temperature is consistent with the setting; turn on the air compressor power (ND) and the host switch in turn; open the test software, and the operating software displays the "READY" status after the instrument is stable; (3) Sample preparation: After the instrument is depressurized, open the sample compartment and take out the sample stage, and fix the sample on the sample with conductive glue. Place the sample stage on the table, load it into the sample chamber and fix it, close the sample chamber; start vacuuming; (4) Sample testing: adjust the acceleration voltage DG to 20KV, ND to 10KV, adjust the working distance DG to 11±1mm, ND to 2mm to 1mm, adjust the current DG to 69uA to 71uA, ND to 2.335A, turn on high voltage, focus, adjust contrast and brightness; (5) Data statistics and calculation: Count the number n and diameter d of microsphere particles with a diameter ≤100nm, and the average particle size is calculated as: X=∑d / n.
[0108] 3. Adhesion test method (1) Disassemble the fully loaded electrode assembly and take out the current collector without the positive electrode material layer; or place the positive electrode sheet in a beaker of N-methylpyrrolidone (NMP), and place the beaker in a 50HZ ultrasonic bath for 10 minutes to remove the positive electrode material layer on the surface; (2) Use dimethyl carbonate (DMC) to wash away the electrolyte or NMP on the surface of the positive electrode sheet; (3) Use dust-free paper to absorb the DMC on the surface of the positive electrode sheet and place it in a fume hood to dry; (4) Place the dried positive electrode sheet in a muffle furnace at 600°C for 2 hours; (5) Take the dried positive electrode sheet and cut the sample with a blade, where The width of the sample is consistent with the width of the double-sided tape, and the length is ≥20mm; (6) Stick the special double-sided tape on the steel plate, the width of the tape is the same as the width of the sample, and the length of the tape is less than the length of the sample; (7) Stick the positive electrode sample cut in step (1) on the double-sided tape, with the test surface facing down; (8) Insert a paper tape with a width equal to the width of the electrode and a length greater than the length of the sample by 80mm to 200mm under the positive electrode, and fix it with wrinkled glue; (9) Turn on the power of the Sansi tensile testing machine, the indicator light is on, and adjust the limit block to the appropriate position; (10) Fix the sample prepared in (7) on the test bench, set the speed to 10mm / min, and start pulling the paper at 90° until the test is completed; (11) Save the test data according to the software prompts, remove the positive electrode after the test is completed, and turn off the instrument.
[0109] 4. Powder loss rate test method (1) Disassemble the fully loaded electrode assembly and take out the current collector without the positive electrode material layer; or place the positive electrode sheet in a beaker of NMP, and place the beaker in a 50HZ ultrasonic bath for 10 minutes to remove the positive electrode material layer on the surface; (2) Use DMC to wash away the electrolyte or NMP on the surface of the electrode sheet; (3) Use dust-free paper to absorb the surface DMC and place it in a fume hood to dry; (4) Under normal temperature environment with humidity ≤75%, cut it into positive electrode sheets with specifications of 100mm×200mm; (5) Fold the positive electrode sheet in half and roll it once with a 2kg roller. The total length of the crease is counted as D. Place the crease of the positive electrode sheet under an optical microscope and measure the powder loss length as d; (6) Brittle powder loss rate = d / D ×100%.
[0110] 5. Diaphragm resistance test method (1) Disassemble the fully loaded electrode assembly and take the current collector without the positive electrode material layer; or place the positive electrode sheet in a beaker of NMP and place the beaker in a 50 Hz ultrasonic bath for 10 min to remove the positive electrode material layer on the surface of the positive electrode sheet; (2) Use DMC to wash away the electrolyte or NMP on the surface of the positive electrode sheet and dry it for 2 h; (3) Connect the power cord of the resistor meter and connect stable compressed air to the pressure regulating valve through a 10 mm air pipe; (4) Turn on the power switch, press the control button, wait for the pressure value to stabilize, and then press the zero button; (5) Open the protective door, take out the sample carrier, and place the cut positive electrode sheet (about 60 (6) Place the sample carrier with the positive electrode sheet into the test chamber, move the sample carrier, snap the test hole to the lower terminal, and close the protective door; (7) Open the electrode resistor meter software, click the test parameter to enter the parameter setting interface, select the single point test mode, and click "Start Experiment" to perform the resistance test; (8) High temperature resistance test: Place the positive electrode sheet in step (2) in a muffle furnace at 600℃ for 2h, dry it to room temperature, and then perform the resistance test according to steps (3) to (7).
[0111] 6. Electrode assembly nail penetration test method (1) Voltage & SOC before nail penetration: 4.5V / 100% SOC; (2) Under the test environment of 20℃±5℃, place the sample on the test table, use a 3mm diameter steel nail to test from the center of the sample at a speed of 150mm / s, and pierce the sample completely; (3) Judgment criteria: no fire, no explosion, no smoke.
[0112] 7. Element mass percentage test A scanning electron microscope was used to determine any 1 μm × 1 μm area at 5 locations, and the mass percentage of phosphorus in all elements was measured using EDS (energy dispersive spectrometer), and the average value was taken to obtain the phosphorus content.
[0113] The test data of each embodiment and comparative example are recorded in Table 1 to Table 8.
[0114] Table 1 Table 2 In combination with Table 1 and Table 2, it can be seen from Examples 1 to 5 that when the first inorganic component contains four elements of lithium, magnesium, zinc and aluminum, under high temperature conditions, the coating can have good adhesion performance and the powder loss rate is the lowest, the positive electrode plate also has a low membrane resistance, and the puncture pass rate of the electrode assembly is also relatively high (all greater than 90%), so that the electrochemical device has good electrochemical performance and excellent high temperature safety performance.
[0115] Compared with Example 4, Examples 6 to 9 changed the mass percentage of the first inorganic component. It can be seen that when the mass percentage of the first inorganic component meets the range of 5% to 30%, the coating has better adhesion performance at high temperature, can better protect the aluminum foil, and make the electrochemical device have excellent high temperature safety performance.
[0116] Compared with Example 4, Examples 10 to 13 changed the mass percentage of phosphorus in the first inorganic component. It can be seen that when the mass percentage of phosphorus meets the range of 5% to 30%, the coating has better adhesion performance at high temperature, can better protect the aluminum foil, and make the electrochemical device have excellent high temperature safety performance.
[0117] Table 3 Table 4 Combining Table 3 and Table 4, compared with Example 4, Examples 14 to 17 change the mass ratio (B / A) of the second inorganic component to the first inorganic component. It can be seen that when B / A satisfies the range of 1.5 to 20, at high temperatures, the adhesion of the coating is greater and the powder loss rate is lower, which makes the high temperature safety performance of the electrochemical device better.
[0118] Compared with Example 4, Examples 18 to 26 further adjust the parameters of the second inorganic component, which is more conducive to improving the safety performance of the electrochemical device at high temperature.
[0119] Table 5 Table 6 In combination with Table 5 and Table 6, compared with Example 4, Examples 27 to 36 are more conducive to improving the safety performance of the electrochemical device at high temperature by further adjusting the mass percentage content and type of the second component, and the mass ratio of the first inorganic component to the second component.
[0120] Table 7 Note: “ / ” in Table 7 means there is no corresponding substance or parameter.
[0121] Table 8 In combination with Table 7 and Table 8, it can be seen from the comparison between Comparative Example 1 and Example 4 that when the first inorganic component is not added to the coating, under high temperature conditions, the diaphragm resistance of the positive electrode plate is small, and at the same time, the adhesion between the current collector and the coating is lower than the case where the coating includes the first inorganic component, the coating powder falls off more seriously, and the puncture pass rate of the electrode assembly is low, which can easily cause short circuit problems, thereby reducing the high temperature safety performance of the electrochemical device.
[0122] From the comparison between Comparative Example 2 and Example 4, it can be seen that when the second inorganic component is not added to the coating, under high temperature conditions, the membrane resistance of the positive electrode plate is small, and at the same time, the bonding force between the current collector and the coating is lower than the case where the coating includes the second inorganic component. The puncture penetration rate of the electrode assembly is low, which can easily cause short circuit problems, thereby reducing the high temperature safety performance of the electrochemical device.
[0123] From the comparison between Comparative Example 3 and Example 4, it can be seen that when the first inorganic component and the second inorganic component are not added to the coating, under high temperature conditions, the membrane resistance of the positive electrode plate is small, and at the same time, the bonding force between the current collector and the coating is lower than that in the case where the coating includes the first inorganic component and the second inorganic component, the coating powder falls off more seriously, and the puncture pass rate of the electrode assembly is low, which can easily cause short circuit problems, thereby reducing the high temperature safety performance of the electrochemical device.
[0124] Therefore, from the above analysis, it can be seen that when the coating includes both the first inorganic component and the second inorganic component, the coating has better adhesion performance under high temperature conditions and maintains better safety resistance, so that the electrochemical device has excellent high temperature safety performance.
[0125] The above implementation modes are only used to illustrate the technical solutions of the present application and are not intended to limit the present application. Although the present application is described in detail with reference to the above implementation modes, a person skilled in the art should understand that the technical solutions of the present application may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode plate includes a current collector, a positive electrode material layer, and a coating layer disposed between the current collector and the positive electrode material layer; The coating includes a first inorganic component including a phosphate containing at least one of lithium, magnesium, zinc, and aluminum, and a second inorganic component different from the first inorganic component.
2. The positive electrode sheet according to claim 1, characterized in that: The phosphate is selected from at least one of lithium dihydrogen phosphate and aluminum dihydrogen phosphate.
3. The positive electrode sheet according to claim 1, characterized in that: Based on the total mass of the coating, the mass percentage of the first inorganic component is A%, 5≤A≤30.
4. The positive electrode sheet according to claim 1, characterized in that: Based on the total mass of the coating, the mass percentage of the first inorganic component is A%, the mass percentage of the second inorganic component is B%, and 1.5≤A / B≤20.
5. The positive electrode sheet according to claim 1, characterized in that: In a 1 μm×1 μm region of the coating, the mass percentage of phosphorus element accounts for 1% to 6% of the mass of all elements.
6. The positive electrode sheet according to claim 5, characterized in that: In a 1 μm×1 μm area of the coating, the mass percentage of the phosphorus element accounts for 3.3% to 6% of the mass of all elements.
7. The positive electrode sheet according to claim 1, characterized in that: The second inorganic component includes at least one of boehmite, aluminum oxide, zinc borate, barium borate, and antimony oxide.
8. The positive electrode sheet according to claim 1, characterized in that: The particle size Dv50 of the second inorganic component is 0.1 μm to 2 μm, and Dv90 is 2 μm to 3 μm.
9. The positive electrode sheet according to claim 1, characterized in that: The coating further comprises a second component, wherein the second component comprises at least one of polyacrylic acid, polypropylene alcohol and sodium carboxymethyl cellulose.
10. The positive electrode sheet according to claim 9, characterized in that: Based on the total mass of the coating, the mass percentage of the first inorganic component is A%, the mass percentage of the second component is C%, 1≤C≤15, and 1≤A / C≤4.
11. The positive electrode sheet according to claim 1, characterized in that: The positive electrode sheet satisfies at least one of the following characteristics: (1) The positive electrode sheet is placed at room temperature, and the film resistance of the positive electrode sheet is 1Ω to 8Ω; (2) The positive electrode plate is placed at a temperature of 600° C. for 2 hours, and the film resistance of the positive electrode plate is 0.8Ω to 2Ω.
12. The positive electrode sheet according to claim 1, characterized in that: The coating satisfies at least one of the following characteristics: (1) The positive electrode sheet is placed at room temperature, and the bonding force between the coating and the current collector is 200 N / m to 800 N / m; the positive electrode sheet is placed at 600° C. for 2 hours, and the bonding force between the coating and the current collector is 10 N / m to 200 N / m; (2) The positive electrode plate is placed at 600°C for 2 hours, and the powder loss rate of the coating is 0.3% to 8%; the positive electrode plate is placed in dimethyl carbonate at 85°C for 2 hours, and the powder loss rate of the coating is 0.5% to 10%.
13. An electrochemical device comprising an electrode assembly, characterized in that: The electrode assembly comprises the positive electrode plate as described in any one of claims 1 to 12, and the pass rate of the nail penetration test of the electrode assembly is 90% to 100%.
14. An electronic device, characterized in that: Comprising the electrochemical device as claimed in claim 13.
Citation Information
Patent Citations
Secondary battery positive electrode and secondary battery
CN110800138A
Electrochemical apparatus and electronic apparatus
WO2022205110A1